The Effect of Mind Mapping Learning Model on Students’ Mathematical Conceptual Understanding of Algebraic Function Derivatives: A Quasi-Experimental Study - Samsuriadi Samsuriadi; Indrawati Indrawati; Muh. Rusmayadi (MASI Mandiri Edukasi, 2026)
Mathematical conceptual understanding is a fundamental competency in secondary mathematics learning, particularly challenging for topics such as algebraic function derivatives. Limited studies have specifically examined mind mapping as a standalone intervention for this topic at the senior high school level in the Indonesian context. This study examines the effect of the mind mapping learning model on students’ mathematical conceptual understanding of algebraic function derivatives. Quasi-experimental pre-test post-test non-equivalent control group; 42 students (23 experimental, 19 control); five-item essay instrument; Cronbach’s α = 0.78; eight instructional meetings; SPSS 29. The findings indicate = 3.478, p = 0.001, Cohen’s d = 1.07; post-test mean experimental (78.43) vs control (69.05). Mind mapping significantly and practically improved conceptual understanding. Mind mapping is a viable alternative strategy for teachers to deepen conceptual mastery of derivative rules.